Capability and orientation of internet of things (IoT) in the world - Sinh, Bach Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
IoT is no longer a prediction, a trend but it is a revolution for development and application of new technologies that are taking place as storms across the world, in the next 5-10 years, it will develop steadily, bearing high efficiency. IoT has the potential to change the Internet-based world, allows information to be shared and decided to be implemented without much human interference. IoT has allowed huge savings on material resources, time and human resources. IoT is applied in many areas and brings many positive effects such as increasing efficiency of fields. However, IoT also has a negative impact on information security and energy consumption to maintain IoT's systems, generating new electronic waste systems in the process of replacing old systems. Code: 17090701